Users' brand page participation - Langaro, Daniela (2022)
Langaro, D., Salgueiro, M. D. F., & Rita, P. (2020). Users' brand page participation: A new construct to measure participation on social networking sites. International Journal of Internet Marketing and Advertising, 14(2), 135-151. https://doi.org/10.1504/IJIMA.2020.107658